A Concept Map of Terminologies and Disciplines for the Executable Model Lifecycle - Lebtag, Bruno G. A.; Teixeira, Paulo G.; Kassab, Mohamad; Graciano Neto, Valdemar Vicente (Anais do Workshop em Modelagem e Simulação de Sistemas Intensivos em Software (MSSiS); 2021: Anais do III Workshop em Modelagem e Simulação de Sistemas Intensivos em SoftwareDO - 10.5753/mssis.2021.17254, 2021)
The Executable Models (ExM) research area is an ascending discipline that explores the use of models capable of being executed during the software development process. The research area is overloaded with terms and concepts derived from several areas. There is also ambiguities and an absence of consensus on definitions. This is a problem not only for newcomers in the area but it can generate unproductive studies and conﬂicts among researchers. However, there is not yet a study presenting those concepts in a concise and structured manner. Thus, this study aims to collaborate with the research area with a collection of relevant concepts and their definitions. The concepts were obtained from a literature review where we collected relevant studies from several disciplines. We organized those concepts into a concept map that establishes the relationship between concepts while presenting them separated by disciplines.